Bioaccessibility Of Essential Lipophilic Nutrients In A Chloroplast-rich Fraction (CRF) From Agricultural Green Waste During Simulated Human Gastrointestinal Tract Digestion - Jutarat Wattanakul; Mansor Syamila; Randa Darwish; Mohamed A. Gedi; Poramat Sutcharit; Chao Chi; Patchaniya Akepach; Moulay Sahaka; Brigitte Gontero; Frédéric Carrière; David A. Gray (Royal Society of Chemistry, 2024)
Indexed by WOS/SCOPUS/ERA